2022
DOI: 10.1007/s40843-021-1891-2
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenated boron-doped carbon via polymer dehalogenation as an electrocatalyst for high-efficiency O2 reduction to H2O2

Abstract: The direct electrochemical synthesis of H 2 O 2 from O 2 is currently the most promising alternative to energyintensive industrial anthraquinone oxidation/reduction methods. However, its widespread use is hampered by the lack of efficient low-cost electrocatalysts. In the current study, oxygenated boron-doped carbon (O-BC) materials were realized via a green synthetic strategy involving polymer dehalogenation and employed as electrode materials for the electrochemical synthesis of H 2 O 2 via a 2e − oxygen red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…530 eV and 281 eV corresponding to O 1s and C 1s, respectively. 50,51 Note that the O 1 s peak is stronger than the C 1s peaks for the CQD sample and the atomic oxygen-to-carbon ratio reaches 30.4 : 69.6, much higher than those of the CSs and the rGQDs and other reported works. 18,19,42 This suggests the ultrahigh O content existing in the CQD samples.…”
Section: Papermentioning
confidence: 68%
“…530 eV and 281 eV corresponding to O 1s and C 1s, respectively. 50,51 Note that the O 1 s peak is stronger than the C 1s peaks for the CQD sample and the atomic oxygen-to-carbon ratio reaches 30.4 : 69.6, much higher than those of the CSs and the rGQDs and other reported works. 18,19,42 This suggests the ultrahigh O content existing in the CQD samples.…”
Section: Papermentioning
confidence: 68%
“…In terms of the B chemical environment, in addition to the effect of B−C and B−N as presented in Figure 2c, the presence of B−O bonding signifies the possible coordination structure of O-BC 2 , which may derive from the point defect upon B doping. 56,57 Such an effect was further studied by DFT calculations. Considering that the B active site is bonded with the N atom, based on the B,Ndoped sp 3 /sp 2 hybrid model, we employ one graphitic N atom equivalent to one C atom to construct the O−BCN structure to represent the point defect model (Figure S16), 58 which is denoted as B,N-doped sp 3 /sp 2 hybrid-v.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Compared with the B,N-doped sp 3 /sp 2 hybrid (Figure f), the N-doped sp 3 /sp 2 hybrid exhibits a higher energy barrier for the formation of *OCHO and a much smaller energy difference between *OCHO and *COOH (Figure S15b), resulting in inferior HCOOH selectivity, which is consistent with the experimental results (Figure S11). In terms of the B chemical environment, in addition to the effect of B–C and B–N as presented in Figure c, the presence of B–O bonding signifies the possible coordination structure of O-BC 2 , which may derive from the point defect upon B doping. , Such an effect was further studied by DFT calculations. Considering that the B active site is bonded with the N atom, based on the B,N-doped sp 3 /sp 2 hybrid model, we employ one graphitic N atom equivalent to one C atom to construct the O–BCN structure to represent the point defect model (Figure S16), which is denoted as B,N-doped sp 3 /sp 2 hybrid-v.…”
Section: Resultsmentioning
confidence: 99%
“…28 Recently, it is found that introducing oxygen-containing groups into carbon can effectively tune the ORR pathway from 4e À to 2e À , implying the possibility of efficient production of H 2 O 2 from O 2 or air, [29][30][31] for instance, O-doped CNTs reported by Cui group, 30 and O-doped carbon nanosheets reported by Liu group. 32 Among all DCMs, N, P co-DCMs typically drive the 4e ORR, as conrmed by many state-of-the-art studies, including the NPMC reported by Dai's group, 33 NPC-4-1100-Zn reported by Xing's group, 34 etc. How to tune the ORR occurring on N, P co-DCMs into the 2e À pathway is intriguing and yet to be explored.…”
Section: Introductionmentioning
confidence: 87%